Adaptation of the Online Student Engagement Scale to Turkish - Gül, Ayşe; Tuncer, Murat (Mehmet Akif KARA, 2025)
Due to the increasing demands for online learning in recent years, there has been an increase in researches to determine the factors affecting students' engagement in classes in these environments. The aim of this research is to adapt a valid and reliable data collection tool to Turkish culture that can be used in evaluating university students' participation in online learning. For this purpose, the online student engagement scale developed by Dixson (2010) was adapted to Turkish. After obtaining the necessary permissions for adaptation from Dixson, who developed the scale adaptation process started. The adaptation study of the scale was carried out with the participation of second, third- and fourth-year undergraduate students studying at Harran University and having experience in online course participation. During the adaptation process of the scale, 211 university students participated in the exploratory factor analysis and 163 university students participated in the confirmatory factor analysis. As a result of exploratory factor analysis, the scale, which originally consisted of 19 items and four dimensions, was reduced to 14 items and three dimensions. As a result of exploratory factor analysis, a three-factor structure was obtained with item factor loadings ranging between .621 and .857. The dimensions of the five-point Likert type scale are named skill-performance, association with life and interaction-participation. In the online student engagement scale adapted to Turkish, the three-factor structure explains 64.29% of the total variance. The three-factor structure that emerged as a result of confirmatory factor analysis and exploratory factor analysis was confirmed, and according to the results of the reliability analysis of the scale, the Cronbach Alpha coefficient was calculated as .918. Cronbach's Alpha reliability coefficient for the dimensions of the scale varies between .813 and .870. As a result of the analysis, it was concluded that the online student engagement scale is valid and reliable in the sample of university students.

Son yıllarda çevrim içi öğrenmeye yönelik taleplerin artmasına bağlı olarak bu ortamlarda öğrencilerin derse katılımını etkileyen faktörlerin belirlenmesine yönelik yapılan çalışmalarda artış görülmektedir. Bu araştırmanın amacı üniversite öğrencilerinin çevrim içi öğrenmeye katılımlarının değerlendirilmesinde kullanılabilecek geçerli ve güvenilir bir veri toplama aracının Türkçeye uyarlanmasını sağlamaktır. Bu amaçla Dixson tarafından geliştirilen çevrim içi öğrenci katılım ölçeği Türkçeye uyarlanmıştır. Ölçeği geliştiren Dixson’dan uyarlama için gerekli izinler alındıktan sonra uyarlama süreci başlamıştır. Ölçeğin uyarlama çalışması Harran Üniversitesinde öğrenim gören ve çevrim içi ders katılım tecrübesi olan ikinci, üçüncü ve dördüncü sınıf lisans öğrencilerinin katılımıyla gerçekleşmiştir. Ölçeğin uyarlanması sürecinde açımlayıcı faktör analizine 211, doğrulayıcı faktör analizine ise 163 üniversite öğrencisi katılmıştır. Açımlayıcı faktör analizi sonucunda orijinali 19 maddeden ve dört boyuttan oluşan ölçek 14 madde ve üç boyuta indirgenmiştir. Açımlayıcı faktör analizi sonucunda madde faktör yükleri .621 ve .857 arasında değişen üç faktörlü bir yapı elde edilmiştir. Beşli likert tipindeki ölçeğin boyutları beceri-performans, hayatla ilişkilendirme ve etkileşim-katılım olarak isimlendirilmiştir. Türkçeye uyarlanan çevrim içi öğrenci katılım ölçeğinde üç faktörlü yapı toplam varyansın %64,29'unu açıklamaktadır. Doğrulayıcı faktör analizi ile açımlayıcı faktör analizi sonucunda ortaya çıkan üç faktörlü yapı doğrulanmış, ölçeğin güvenirlik analizi sonucuna göre Cronbach Alfa katsayısı .918 olarak hesaplanmıştır. Ölçeğin boyutlarına ilişkin Cronbach Alfa güvenirlik katsayısı .813 ile .870 arasında değişmektedir. Analizler sonucunda çevrim içi öğrenci katılım ölçeğinin üniversite öğrencileri örnekleminde geçerli ve güvenilir olduğu sonucuna ulaşılmıştır.
Çevrim İçi Öğrenci Katılım Ölçeğinin Türkçeye Uyarlanması
Keywords: Cross-Cultural Scale Adaptation; Kültürlerarası Ölçek Uyarlama